2021
DOI: 10.3390/ijerph18147707
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Personality in the Relationship between Internet Use and Study Abroad Difficulties

Abstract: Studying abroad can be stressful due to culture shock and various other difficulties. However, with the current prevalence of information communication technology, we can surmise that study abroad difficulties should be minimal. Since it has been shown that an individual’s personality is highly associated with their internet use behaviors, it would be interesting to determine the effects of personality traits on the relationship between internet use motives and perceived study abroad difficulties. Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 88 publications
(93 reference statements)
2
4
0
Order By: Relevance
“…In line with the approach of the pervasive effects of personality traits in different social, familial, and even work contexts (Ching, 2021), the current study's findings showed that there is a stronger positive relationship between motheroriented perceived family atmosphere and academic performance, as well as between father-oriented perceived family atmosphere and academic performance, at higher levels of conscientiousness compared to lower levels. This means that when conscientiousness in students is high, the relationship between perceived family atmosphere and academic performance is stronger.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In line with the approach of the pervasive effects of personality traits in different social, familial, and even work contexts (Ching, 2021), the current study's findings showed that there is a stronger positive relationship between motheroriented perceived family atmosphere and academic performance, as well as between father-oriented perceived family atmosphere and academic performance, at higher levels of conscientiousness compared to lower levels. This means that when conscientiousness in students is high, the relationship between perceived family atmosphere and academic performance is stronger.…”
Section: Discussionsupporting
confidence: 84%
“…This means that when conscientiousness in students is high, the relationship between perceived family atmosphere and academic performance is stronger. This finding supports the pervasive effects approach of conscientiousness as a personality trait (Ching, 2021) and implies that considering both environmental factors like family atmosphere and personality traits is realistic and necessary when examining variables influencing students' academic performance. The mentioned relationships occur because parents who can create a positive emotional atmosphere in the family are responsible and conscientious, accepted by their children as role models due to the bond based on respect and emotional exchange.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In the C3, though, we saw that students showed some decline in the DO. Prior studies (Ching, 2021) have argued that some of the potential reasons for the decrease could be because students experience culture shock while studying abroad, or they may not feel comfortable interacting with people from other cultures. Studies (Ching, 2021;Kim & Okazaki, 2014) have also indicated that students who are younger in age may find studying abroad a difficult experience.…”
Section: Discussionmentioning
confidence: 99%